Naval powers in the Indian Ocean and the Western Pacific - Hensel, Howard M. 1946-; Gupta, Amit 1958- (Routledge, Taylor & Francis Group, 2018)
"In previous years, many scholars and policy makers have traditionally viewed portions of the Indian Ocean and the Western Pacific as separate and discrete political, economic, and military regions. In recent years, however, a variety of economic, political, and military forces have made many within the academic community, as well as a growing number of national governmental leaders, change their perceptions and view these maritime expanses as one zone of global interaction. As a consequence, political, military, and economic developments in one maritime region increasingly have an impact on the other regions. Analyzing and assessing the perceptions, interests, objectives, maritime capabilities and policies of the major maritime powers operating in this area, as well as the contemporary maritime challenges and opportunities, this valuable study highlights the current prospects for peace and security and evaluates possible alternative scenarios for future developments in what is rapidly becoming recognized as an integrated zone of global interaction."...Provided by publisher